2016
DOI: 10.1038/mi.2015.111
|View full text |Cite
|
Sign up to set email alerts
|

A pathogenic role for tumor necrosis factor-related apoptosis-inducing ligand in chronic obstructive pulmonary disease

Abstract: Chronic obstructive pulmonary disease (COPD) is a life-threatening

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
110
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(121 citation statements)
references
References 54 publications
10
110
0
1
Order By: Relevance
“…In this study, we investigated the mechanisms involved using our established experimental systems (27,(32)(33)(34). We found that COPD pBECs and mice with experimental COPD infected with IAV have higher levels of inflammatory cytokines but reduced antiviral responses (30,35). We uncovered that NF-κB-mediated inflammation in IAV infection and in COPD was also exaggerated and resulted from decreased levels of A20 protein, which in turn was caused by elevated levels of miR125a or -b.…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations
“…In this study, we investigated the mechanisms involved using our established experimental systems (27,(32)(33)(34). We found that COPD pBECs and mice with experimental COPD infected with IAV have higher levels of inflammatory cytokines but reduced antiviral responses (30,35). We uncovered that NF-κB-mediated inflammation in IAV infection and in COPD was also exaggerated and resulted from decreased levels of A20 protein, which in turn was caused by elevated levels of miR125a or -b.…”
Section: Introductionmentioning
confidence: 96%
“…In vivo. Experimental COPD and influenza infection were induced; miR-125a and -b were inhibited using specific antagomirs; and histopathology, IHC, immunoblotting, and cytometric bead array and data analyses were performed as previously described and/or as in Supplemental Methods (33,35,39,(59)(60)(61)(62)(63)(64)(65)(66)(67).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Analyzing BALf is one of the prime parameters to understand the underlying disease pathology in prominent mice models of major respiratory diseases, including asthma [27][28][29], COPD [30,31], and pulmonary fibrosis [32]. Moreover, the application of BALF is not only restricted to quantifying the inflammatory cells, it is also employed to determine the viral titre in various viral infections [3,30].…”
Section: Clinical Utility Of Balf Collectionmentioning
confidence: 99%